The ministry of utmost happiness / Arundhati Roy. - Roy, Arundhati (Hamish Hamilton, 2017)
'The Ministry of Utmost Happiness' transports us across a subcontinent on a journey of many years. It takes us deep into the lives of its gloriously rendered characters, each of them in search of a place of safety - in search of meaning, and of love.